La divulgación de la información como causal de visto bueno para la terminación de un contrato de trabajo, emitido por el empleador dentro de la normativa laboral - Ruiz Mayancha, Jomayra Viviana (2024)
ABSTRACT Currently, the employment relationship that exists between the employer and the worker has become complicated due to several questions and situations where the disclosure of information has turned into a problem that affects in a direct way the productive development of both the company and the people who direct it. In any case, it is very common that certain companies, when signing a contract, include within the contract a clause that indicates the employer or worker that they are responsible and custodian of certain information which must not be disclosed nor shared because in many cases this is used only for strictly labor affairs; otherwise, this would originate economic, social and working prejudice. On the other hand, one of the main causes that is established in our current Labor Code is the juridical figure of approval, legal and appropriate mechanism that allows a labor relationship between employers and workers to be ended, this legal procedure must be sustained and supported to avoid the violation of the rights of the workers because this can be the subject of countless compensations payments which in some cases would not be granted to workers who have had inappropriate and unsuitable behaviors that are not well seen by the employer. Although it is true that the Article 310, number 1 of the Labor Code establishes that at the time of disclosure of information by a worker, the employer has the faculty to finish the labor contract and apply the approval, under these circumstance it is necessary to emphasize the risk that some employers are exposed to when there is employee disloyalty considering that it leads them to a legal loophole that increases the risk of prejudice to the company. For this reason, it is necessary to implement a labor reform to the Labor Code giving the employer the faculty to be able to protect their corporate and business interests in the Article 172 to include the number 8 that entails the following text: “When the worker reveals secrets, makes disclosures or violates confidentiality clauses causing harm to the employer”; taking into account its agreement with the Article 310, number 1 of this Code.